A PRESENTATION OF EXTREMAL FUNCTIONS IN THE EXPLICIT FORM FOR THE WIDE CLASS OF LINEAR FUNCTIONALS ON H1 - SPACE - V.G. RYABYKH; G.Y. RYABYKH (Advanced Engineering Research)
В работе найдены в явном виде экстремальные функции для широкого класса функционалов над пространством Харди H 1 .